CAPACIDADE DE USO DA TERRA E PERDA DE SOLO EM UMA PROPRIEDADE REPRESENTATIVA NA BACIA HIDROGRÁFICA DO RIO DO ATALHO, CRUZ MACHADO – PR. - Marinheski, Vanderlei (2011)
This study sought to evaluate the contribution of different sources producing in sediment on a representative property in river basin of the shortcut, Cruz Machado, PR, and through utility survey of the physical environment in the basin was proposed map a capacity of land use to basin and a in specific for property in representative. The property has a representative system of family farms with low technological level and with the use of rudimentary tools (sickle, hoe use and animals to till the soil), relief is characterized by the constant presence of blocks and boulders of igneous rocks, beyond the steep slopes of the slopes, features that predominate in other properties of the basin and the region as a whole. To measure the erosion were installed plots with erosion pins in a crop of corn, mate, pasture, an area near the house and four snippets of rural roads inside the property, and two stretches of road outside a property on the road general of the basin and the other with access from the house of a farmer in general road, these two have paved with gravel. With the monitoring of parcels and profiles of roads for a year, there were levels of soil removal at each pin or mediated profile road. The results indicate the removal of soil above the tolerance levels for soil characteristics, especially on roads and crop areas. The maps of land use capacity of the basin and representative of the property indicate that more than half of the areas have no aptitude for agriculture and should be used for permanent crops or preserving the flora and fauna..